Theory and method in higher education research. Vol. 1 - Huisman, Jeroen; Tight, Malcolm (Emerald, 2015)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. Theory and method in higher education research I contains contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education.
Keywords: Education -- Higher.; Higher & further education, tertiary education.; Education, Higher -- Research.; Education, Higher -- Research -- Methodology.; elektronické knihy; electronic books